The Relationship Between Work Period Length, Transactional Leadership Style, and Employee Engagement on Employee Work Performance at Factory X - Christina Valeria Sie; Lois Scarlet; Annisa Kusuma (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research aims to examine the relationship between work period length, transactional leadership style, and employee engagement with employee performance at Factory X. Employee performance serves as a key indicator of an organization's productivity and can be influenced by a variety of individual and managerial factors. Leadership styles are generally categorized into transformational and transactional. Transactional leadership emphasizes the exchange process between leaders and subordinates, relying on a system of rewards and punishments to motivate employees, which may affect their level of engagement and performance. Furthermore, the duration of an employee’s work period can reflect their experience and level of adjustment within the workplace. A quantitative approach is used in this study, employing surveys directed at employees of Factory X. Data collection is carried out through questionnaires, and the results are analyzed using SPSS (Statistical Package for the Social Sciences) through descriptive statistics, validity and reliability tests, Pearson correlation, and multiple linear regression. These analyses aim to assess the relationship between the independent variables (work period length, transactional leadership, and employee engagement) and the dependent variable (employee performance). The findings of this study are intended to support corporate organizations in optimizing human resource management to enhance employee performance.